Heavy Metals Contents and Histopathological Analysis of Some Organs of Fish Obtained from Payau River, Anggana, Kutai Kartanegara, Indonesia - Sulistyawati Hidayat; Iwan Suyatna; Ahmad Rafii; Ghitarina Ghitarina (Center for Journal Management and Publication, 2020)
The objectives of this study were to determine the heavy metals contents (Cd, Pb, Cu and Zn) in the body of some freshwater fish and to examine the histopathological changes of some organs. The fish were obtained from Payau River located in Anggana, Kutai Kartanegara District, East Kalimantan, Indonesia. There were four (4) species examined namely: Glass Fish (Chanda sp), Croaker (Micropogenias undulatus), Lais (Kryptopterus cryptopterus), and spotted catfish (Arius maculatus). Lead (Pb), Cadmium (Cd), Copper (Cu), and Zinc (Zn) were being analysed in the gills, livers, and the muscles of the fish. The results showed that Pb and Cd were still low and fulfilled the the quality standard based on Indonesian National Standards Agency (INSA, 2009) and Directorate of Drug and Food Control No. 03725/B/SK/VII/89. Cadmium concentration in the fish organ was < 0.003 mg/kg (Max. limit of Quality standard is 0.1 mg/kg) and Pb concentration was <0.002 mg/kg (Quality standard is 0.3 mg/kg). Yet, Cu and Zn concentrations were exceeded the Quality standard as the levels were 2.63-2.93 mg/kg and 60.23 -65.55 mg/kg., respectively. Based on Histopathological analysis of the gills, livers and muscles, the fish experienced edema, hyperplasia, vacuolar degenerative, necrosis and hemorrhagic ..